Diversidad de hongos filamentosos en dos tipos de bosques del arboretum el huayo Loreto 2021 - Bendayán Acosta, María Elena (2023)
In the study carried out at the Zungarococha Farm of the National University of the Peruvian Amazon (Puerto Almendras) during the months of August to October 2021, the diversity of filamentous fungi was evaluated in two types of forests: flooded and non-flooded. Three study points were identified in each type of forest using the Omeliansky static method with Petri dishes and Potato Dextrose Agar, sampling every 15 days. A total of 1564 filamentous fungi were recorded, belonging to 2 divisions, 5 classes, 9 orders, 13 families and 60 species. Species diversity was slightly higher in the non-flooded forest, which also showed a higher abundance of records. In the flooded forest, the most abundant species were Fusarium sp. 7, Penicillium sp. 4 and Pestalotiopsis oryzae, each with 16 records, followed by Penicillium sp. 9 (12 records) and Fusarium moniliforme (11 records). In the non-flooded forest, the most abundant species was Aspergillus niger with 22 records, followed by Pestalotiopsis oryzae (21 records), Penicillium sp. 4 (13 records), Fusarium moniliforme and Penicillium crystallinum (12 records each). Both forest types shared 42% of the species. Unique species were recorded, such as Helminthosporium sp. 1 and Phialophora sp. 1 in the flooded forest, and Penicillium sp. 12 and Chaetomiun sp. 2 in the non-flood forest.